2015
DOI: 10.9734/ijpss/2015/14519
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Soil Chemistry to Enhance Heathland Recreation: A Use for Sulphur Captured During Oil Refining

Abstract: The overall aim of this paper is to evaluate potential new modifications to methods for re-creating heathland habitats. Heathlands need acidic soils so the specific objectives are to evaluate the effectiveness of a new method for heathland re-creation by soil acidification using a sulphur soil amendment and to explore the benefits for re-creation of applying a soil stripping treatment in conjunction with soil acidification. A new source of sulphur was recovered from oil refinery towers and applied over agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Application of elemental sulphur has resulted in the chemical conditions in the acidified pasture being significantly different to the control pasture, both in terms of multivariate analysis of similarity (ANOSIMchem) and Heathland Restoration Index (HRIchem). Soil pH and phosphorus have been found to drive aboveground floral community composition in heathland and grassland systems [69][70][71] and low pH and P concentrations are characteristic of the native heathland in this study [22] Table 8 summarizes the significant differences observed between the control pasture and the acidified pasture, and the acidified pasture and heathland. According to ANOSIM, regardless of the variables used (chemical, microbial faunal, or a combination), the acidified pasture treatment was significantly different to the control pasture.…”
Section: Aboveground Response To Changes In Soil Chemical Propertiesmentioning
confidence: 77%
“…Application of elemental sulphur has resulted in the chemical conditions in the acidified pasture being significantly different to the control pasture, both in terms of multivariate analysis of similarity (ANOSIMchem) and Heathland Restoration Index (HRIchem). Soil pH and phosphorus have been found to drive aboveground floral community composition in heathland and grassland systems [69][70][71] and low pH and P concentrations are characteristic of the native heathland in this study [22] Table 8 summarizes the significant differences observed between the control pasture and the acidified pasture, and the acidified pasture and heathland. According to ANOSIM, regardless of the variables used (chemical, microbial faunal, or a combination), the acidified pasture treatment was significantly different to the control pasture.…”
Section: Aboveground Response To Changes In Soil Chemical Propertiesmentioning
confidence: 77%
“…Indeed, even after nearly 150 years (albeit with minimal additional management; i.e. grazing by livestock), soil chemistry failed to approach the levels of acidity, organic content, CEC, or key soil nutrients characteristic of, and important in, heathland soil (Clarke ; Green et al ). Similarly, although some species typical of established ALH were abundant in the 1868 site, the community was also characterized by species representative of acid or mesotrophic grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low pH often results in loss of cations from soils; e.g. Green et al () reported a positive correlation between pH and concentrations of extractable K, Ca, and Mg, but a negative association with phosphate. In turn, soil concentrations of many elements affect the bioavailability of other key nutrients and also influence greatly the growth of species that might otherwise outcompete the target heathland species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations